2015
DOI: 10.1007/s00381-015-2897-x
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation during pregnancy: an instructive case

Abstract: A confirmation of VNS safety may increase its use during pregnancy, thus reducing possible systemic effects of antiepileptic drugs and antidepressants on the women and the baby.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…Although device functioning was not optimal during the critical period of organogenesis, no morphologic abnormalities of the fetus were detected. 11…”
Section: Discussionmentioning
confidence: 99%
“…Although device functioning was not optimal during the critical period of organogenesis, no morphologic abnormalities of the fetus were detected. 11…”
Section: Discussionmentioning
confidence: 99%
“…Pilot studies in animal models also failed to find teratogenic effects of VNS . A potential benefit of VNS during gestation is the possibility of AEDs reduction in number or dosage, as seen in patient 4 . One concern with VNS could be the possible effect of a malfunctioning system, but a case was reported with suboptimal device functioning detected during the organogenesis period with no morphological abnormalities of the fetus .…”
Section: Discussionmentioning
confidence: 99%
“…A potential benefit of VNS during gestation is the possibility of AEDs reduction in number or dosage, as seen in patient 4 . One concern with VNS could be the possible effect of a malfunctioning system, but a case was reported with suboptimal device functioning detected during the organogenesis period with no morphological abnormalities of the fetus . On the other hand, VNS could safely continue functioning during delivery, either during vaginal birth or during cesarean section.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 23 VNS has been used successfully as a treatment for medically refractory epilepsy in pregnant women, and physicians have concluded that VNS is a viable option for treatment during pregnancy. 24 , 25 As a non-pharmacological treatment, VNS seems to be beneficial for seizure control in the expecting mother, and there is no evidence of harm to the developing fetus. To date, no large clinical trials have been performed to assess whether VNS has a long-term effect on the developing fetus.…”
Section: Current Clinical Uses Of Vnsmentioning
confidence: 99%